The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0036-46652007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping, serotyping and determination of mating-type of Cryptococcus neoformans clinical isolates from São Paulo State, Brazil

Abstract: SUMMARYThe basidiomycetous yeast Cryptococcus neoformans is an important fungal pathogen mainly in immunocompromised patients. In this study, 47 clinical isolates of C. neoformans from regions of São Paulo State were studied serologically by using the Crypto Check Iatron RM 304-K kit, their genetic diversity was estimated by PCR-fingerprinting with a microsatellite-specific sequence (GACA) 4 , RAPD with primer 6 (Amersham Pharmacia Biotech), PCR-restriction fragment length polymorphism (RFLP) analysis of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 47 publications
(64 reference statements)
3
22
0
1
Order By: Relevance
“…However, in Brazil, molecular epidemiology studies are still required to elucidate the distribution of molecular types in all five Brazilian regions. Despite this, the few epidemiological studies conducted in Brazil have demonstrated differences in the distribution of the genotypes of these species in these regions [17][18][19][20][21]36]. In Mato Grosso, this is the first report describing the molecular types circulating in the state capital of Cuiabá.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, in Brazil, molecular epidemiology studies are still required to elucidate the distribution of molecular types in all five Brazilian regions. Despite this, the few epidemiological studies conducted in Brazil have demonstrated differences in the distribution of the genotypes of these species in these regions [17][18][19][20][21]36]. In Mato Grosso, this is the first report describing the molecular types circulating in the state capital of Cuiabá.…”
Section: Discussionmentioning
confidence: 88%
“…C. neoformans is the species with the largest number of isolates among species belonging to the Cryptococcus complex [5,[16][17][18]37]. Currently, an increasing number of cases of cryptococcosis have been reported in patients without HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few Brazilian studies have investigated the molecular types of environmental Cryptococcus 1,2,3,22,24,28,35 . The distribution of molecular types using the specific primer M13 shows the predominance of VNI (serotype A) in surveyed regions.…”
mentioning
confidence: 99%
“…It is worthwhile to note the presence of VNIV (serotype D) in eucalypt trees in the deep south of Brazil, a subtropical region 2,28 , and of VGI (C. gattii serotype B) in excreta of psittaciformes in the same region 1 . Study of clinical isolates in São Paulo showed that all of them were serotype A and the majority belonged to the molecular type VNI 22 .…”
mentioning
confidence: 99%